A construção coparticipativa da polícia de segurança e a implantação de núcleo interdisciplinar de educação em direitos humanos na Polícia Militar do Tocantins - Santos, Sérgio Nunes dos (Universidade Federal do Tocantins, 2021)
The fight against urban violence in the country is implemented through different strategies and institutional instruments. Given this and the role assigned to public security, by the 1988 constituent, of being eminently preventive, the need arose, given the high rates of violence recorded in the country - especially in the northern region in recent decades - to analyze the guidelines of the strategy of Community Police, especially those present in the states of the Northern Region. The concept of Community Police says that it is a public security strategy that highlights the partnership between the population and the police, which is one of the most widespread concepts among scholars on the subject, and is also present in the National Community Police Directive in Brazil (Ordinance No. 43, May 12, 2019). So, in order to analyze the compatibility between the Community Police guidelines existing in the North Region and the legislative creation of an interdisciplinary human rights education nucleus, within the scope of the Military Police of Tocantins, a documental, bibliographical and also, a questionnaire was sent to the Military Police of this region, whose purpose was to investigate what are the main guidelines of the Community Police strategy, present in these institutions and how such guidelines and practices were dealt with by local legislation. In the state of Tocantins, for example, the Community Police strategy, as an alternative to that vision of distancing the police and the community, is already a reality. There is even an attempt by the Institution, through an internal instrument, called SOP – Standard Operating Procedure, to standardize the actions developed, based on the application of Community Police guidelines, present in the Corporation. Therefore, it is concluded that an interdisciplinary center of human rights education is fully compatible with the preventive nature of public security and the Military Police, as a permanent institution. In addition, as it exists nationally and in the North Region, extensive experience with the Community Police strategy that seeks, precisely, to bring the community closer to the Institution, the creation of an interdisciplinary nucleus, would constitute an amplifying instrument for this approximation and partnership, it may represent a milestone in public safety in Tocantins.